The role of civil society organizations in the struggles for human rights and democracy in Mexico - Cedano, Pablo Romo (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
Organizations specializing in civil society human rights in Mexico have evolved, creating a context of greater democracy. Its growth and professionalization were achieved due to the great social movements that generated processes of great change in the country. These bodies are an instrument of society to promote, strengthen, defend and promote human rights. Its agenda changes according to the territory conquered by democracy in the country.
Keywords: Human rights defenders (HRDs). Protection mechanisms. Self-protection. Risk. Extreme rightist.